Sexually transmitted infection screening uptake and knowledge of sexually transmitted infection symptoms among female sex workers participating in a community randomised trial in Peru. (April 2016) - Kohler, Pamela K; Campos, Pablo E; Garcia, Patricia J; Carcamo, Cesar P; Buendia, Clara; Hughes, James P; Mejia, Carolina; Garnett, Geoff P; Holmes, King K
This study aims to evaluate condom use, sexually transmitted infection (STI) screening, and knowledge of STI symptoms among female sex workers in Peru associated with sex work venues and a community randomised trial of STI control. One component of the Peru PREVEN intervention conducted mobile-team outreach to female sex workers to reduce STIs and increase condom use and access to government clinics for STI screening and evaluation. Prevalence ratios were calculated using multivariate Poisson regression models with robust standard errors, clustering by city. As-treated analyses were conducted to assess outcomes associated with reported exposure to the intervention. Care-seeking was more frequent in intervention communities, but differences were not statistically significant. Female sex workers reporting exposure to the intervention had a significantly higher likelihood of condom use, STI screening at public health clinics, and symptom recognition compared to those not exposed. Compared with street- or bar-based female sex workers, brothel-based female sex workers reported significantly higher rates of condom use with last client, recent screening exams for STIs, and HIV testing. Brothel-based female sex workers also more often reported knowledge of STIs and recognition of STI symptoms in women and in men. Interventions to promote STI detection and prevention among female sex workers in Peru should consider structural or regulatory factors related to sex work venues.